Caffeic acid on metabolic syndrome: A review - Nellysha Namela Muhammad Abdul Kadar; Fairus Ahmad; Seong, Lin Teoh; Mohamad Fairuz Yahaya (Molecular Diversity Preservation International, 2021)
Metabolic syndrome (MetS) is a constellation of risk factors that may lead to a more sinister disease. Raised blood pressure, dyslipidemia in the form of elevated triglycerides and lowered highdensity lipoprotein cholesterol, raised fasting glucose, and central obesity are the risk factors that could lead to full-blown diabetes, heart disease, and many others. With increasing sedentary lifestyles, coupled with the current COVID-19 pandemic, the numbers of people affected with MetS will be expected to grow in the coming years. While keeping these factors checked with the polypharmacy available currently, there is no single strategy that can halt or minimize the effect of MetS to patients. This opens the door for a more natural way of controlling the disease. Caffeic acid (CA) is a phytonutrient belonging to the flavonoids that can be found in abundance in plants, fruits, and vegetables. CA possesses a wide range of beneficial properties from antioxidant, immunomodulatory, antimicrobial, neuroprotective, antianxiolytic, antiproliferative, and anti-inflammatory activities. This review discusses the current discovery of the effect of CA against MetS.